2009
DOI: 10.14704/nq.2009.7.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Quantum State Reduction by a Physical Interaction Between the States and its Perspective for Biology

Abstract: A phenomenological model for the calculation of reduction probabilities of a superposition of several states is presented, which bases only the idea that quantum state reduction has its origin in a physical interaction between the states. The model is explicitly worked out for the hypothesis of gravity-induced quantum state reduction. It agrees for typical quantum mechanical experiments with the projection postulate and predicts regimes in which other behaviour could be observed. For verification a feasible qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, this must not be taken as if the field of quantum theory in general belongs only or mainly to the microscopic universe [38]. We would like to highlight that rather than thinking in volume and size, the quantum reality [39] refers, still better, to time, namely, microscopic times and processes.…”
Section: Non-trivial Quantum Effects Revisitedmentioning
confidence: 99%
“…However, this must not be taken as if the field of quantum theory in general belongs only or mainly to the microscopic universe [38]. We would like to highlight that rather than thinking in volume and size, the quantum reality [39] refers, still better, to time, namely, microscopic times and processes.…”
Section: Non-trivial Quantum Effects Revisitedmentioning
confidence: 99%
“…Indeed, quantum effects have been observed or proposed to play a role in phenomenon involving enzymes, DNA, brain microtubules, and very recently the operation of the avian compass (Engel et al 2007;Hosten and Kwiat 2008;Patel 2001;Davies 2004;Ogryzko 1997;Genovese 2003;Cooper 2009;Rieper et al 2009;Home and Chattopadhyaya 1996;Quandt-Wiese 2009). Experimental physics has revealed the quantum nature of large molecules such as C 60 Buckyball (Arndt et al 1999) the fluorofullerene C 60 F 48 molecule (Hackermuller et al 2003) and recently mechanical systems have also been observed to display quantum properties (Jost et al 2009).…”
Section: Quantum Mechanics and Biologymentioning
confidence: 99%